Histology and Long-term Clinical Outcome of Crushed Cartilage with Double-layer Gelatin Sponge Membrane for Dorsum Refinement in Primary Rhinoplasty - Nocini, Riccardo; Abdulraheem, Maryam; Galzignato, Pier-Francesco; Manzini, Jessica; Bernardi, Paolo; Conti, Giamaica; Sbarbati, Andrea; Chirumbolo, Salvatore; Bertossi, Dario (Facial Plastic Surgery, 2023)
This article demonstrates the ability to use autologous crushed cartilage grafts in rhinoplasty with rapid recovery and optimal nasal functionality without any tissue damage and allows its rapid rejuvenation. Eligible patients underwent primary rhinoplasty using autologous crushed cartilage graft followed by microscopy imaging of the grafted tissue after recovery. Tissue and cytological analysis using optical microscopy, transmission electronic microscopy (TEM), and scanning electronic microscopy (SEM) showed complete viability of chondrocytes, formation of new collagen fibers, neo-perichondrium, neo-angiogenesis, and exhibiting optimal aesthetic outcome. The surgical approach is easy to perform, feasible, and less time-consuming, with excellent tissue rejuvenation and rapid recovery.
Keywords: crushed cartilage; histology; rhinoplasty; nasal dorsum; surgery